Effect of supply chain planning of liquid nitrogen and frozen semen on the quality of animal breeding public services in the selected cattle corridor districts of Uganda - Lagu, Charles; Kugonza, Sylvester; Nagitta, Oluka Pross; Andama, Morgan (International Journal of Agricultural Policy and Research, 2020)
The study aimed to explain the effect of supply chain planning of liquid nitrogen and frozen semen on the quality of animal breeding public services in the selected cattle corridor districts (Mbarara, Mubende, Luwero and Soroti) of Uganda. The research filled the gap of supply chain planning in ensuring proficient and viable supply of animal breeding inputs from supply chain points of view compared to the traditional core science orientation which tend to focus on the biological processes of reproductive technologies. The study adopted cross-sectional survey design embracing both qualitative and quantitative approaches. Data was captured using structured questionnaires, review of records, focus group discussions (FGDs) and key informant interviews (KIIs) for farmers, staff of the National Animal Genetic Resources and Data Bank (NAGRC&DB), artificial insemination (AI) technicians, and Field Extension workers. The study points to gender disparity as a key concern at household levels when it comes to land and animal ownership. The study established that there was positive relationship between planning (χ2=4.270; p=0.039; χ2critical=3.841) and animal breeding services in selected cattle corridor districts of Uganda. The study recommends that genetic centres to put in place systems for coordinated and integrated planning to facilitate outreach for AI services in Uganda.
Keywords: Animal resources; Artificial insemination services; Breeding inputs; Gender disparity; Genetic centre; Quality